SIKLUS TUJUH TAHUNAN EKONOMI INDONESIA (1931-1966-2001-2036) - Mubyarto Mubyarto (Faculty of Economics and Business, Universitas Gadjah Mada, 2001)
Indonesian economy has been experiencing 7 year cycle starting the year of independence in 1945. In a larger cycle, the economic and political crises took place every 35 years (5 x 7 years), hence the crisis of 1931, 1966, and 2001. There are also 3 x 7 years historical “repeat” in the national debate of Indonesian economy i.e., the year of 2001, 1980, and 1959. The year of 1959 was important in Indonesian economic history because it was the year when Indonesia decided to return to the 1945 Constitution after the “konstituante” (Constitution Making Body) failed to make a new constitution. It is important to note that social justice for the whole Indonesian people is the final goal of national development where equity and justice is observed and poverty is eradicated. Indonesian economy can best be analyzed by moral economy and transdiscriptinary approach rather than strict neoclassical economy theory. That is why many economists were surprised by the coming of Indonesias monetary crises.